Investigating Community Pharmacy Take Home Naloxone Dispensing during COVID-19: The Impact of One Public Health Crisis on Another - George Daskalakis; Ashley Cid; Kelly Grindrod; Michael A. Beazely (MDPI AG, 2021)
A recent report found that the number of opioid-related deaths in Ontario in the first 15 weeks of the COVID-19 pandemic was 38.2% higher than in the 15 weeks before the pandemic. Our study sought to determine if pharmacy professionals self-reported an increase or decrease in naloxone provision due to the pandemic and to identify adjustments made by pharmacy professionals to dispense naloxone during the pandemic. A total of 231 Ontario community pharmacy professionals completed an online survey. Pharmacy professionals' barriers, facilitators, and comfort level with dispensing naloxone before and during the pandemic were identified. The sample consisted of mostly pharmacists (99.1%). Over half (51.1%) reported no change in naloxone dispensing, while 22.9% of respondents reported an increase and 24.7% a decrease. The most common adjustments made during the pandemic were training patients how to administer naloxone over video or phone, delivering naloxone kits, and pharmacy technicians offering naloxone at prescription intake. Over half (55%) of participants said the top barrier for dispensing was that patients did not request naloxone. Naloxone distribution through pharmacies could be further optimized to address the increased incidence of overdose deaths during the pandemic. Future research should investigate the reasons for changes in naloxone dispensing.